2009
DOI: 10.1021/la901639h
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Bovine (BSA), Rabbit (RSA), and Porcine (PSA) Serum Albumins with Cationic Single-Chain/Gemini Surfactants: A Comparative Study

Abstract: The interactions among bovine, rabbit, and porcine serum albumins and single-chain cationic surfactant cetyltrimethylammonium bromide (CTAB) versus its gemini counterpart (designated as G4) have been studied. The studies were carried out in an aqueous medium at pH 7.0 using UV, intrinsic and extrinsic fluorescence spectroscopy, and far-UV circular dichroism techniques. The results indicate that compared to CTAB, G4 interacts strongly with the serum albumins, resulting in a significantly larger unfolding or dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(47 citation statements)
references
References 48 publications
4
42
0
1
Order By: Relevance
“…This confirms the conclusion that imidazolium surfactants interact with BSA more strongly than quaternary ammonium surfactants with the same hydrophobic chain. The explanations may be that imidazolium surfactants display the strong p-p interaction, namely, the aromatic ring stacking between the imidazolium rings and the residues (such as Trp, Tyr, and Phe) in BSA, besides electrostatic and hydrophobic interactions [39,40,47], attributing to the existence of aromatic functional groups imidazolium ions for [C n -4-C n im]Br 2 or [C 12 mim]Br. This aromatic ring stacking leads to the more expanding of polypeptide and the larger unfolding of BSA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This confirms the conclusion that imidazolium surfactants interact with BSA more strongly than quaternary ammonium surfactants with the same hydrophobic chain. The explanations may be that imidazolium surfactants display the strong p-p interaction, namely, the aromatic ring stacking between the imidazolium rings and the residues (such as Trp, Tyr, and Phe) in BSA, besides electrostatic and hydrophobic interactions [39,40,47], attributing to the existence of aromatic functional groups imidazolium ions for [C n -4-C n im]Br 2 or [C 12 mim]Br. This aromatic ring stacking leads to the more expanding of polypeptide and the larger unfolding of BSA.…”
Section: Resultsmentioning
confidence: 99%
“…As seen in Fig. 6, the CD spectra of BSA exhibit two negative bands in the UV region at 208 and 222 nm, which is the characteristic of the a-helical structure of protein [22,40,48]. At low [C 12 -4-C 12 im]Br 2 concentrations (60.002 mmol L À1 ), there is little change in the negative ellipticity at 208 and 222 nm, but at high concentrations (>0.01 mmol L À1 ), the negative ellipticity decreases.…”
Section: The Change Of Bsa Secondary Structure In the Presence Of Surmentioning
confidence: 85%
See 1 more Smart Citation
“…This also encourages the interest in researching the synthesis of simple and practical surfactants and developing desirable methods in proteomic research. Recently, protein-gemini surfactants interactions have been developed because these surfactants have a low critical micelle concentration (CMC), a low Krafft temperature, a strong hydrophobic microdomain, and a superior viscous behavior in comparison to the conventional single-chain surfactants [15][16][17][18]. However, the complex synthesis and purification procedures associated with these surfactants often lead to expensive consumption which limits the application of gemini surfactants in proteomic research.…”
Section: Introductionmentioning
confidence: 99%
“…Within mammalian systems, albumins show high sequence similarity of gene sequence, hence structure and function [1]. But very few works have been done to understand variations in physical properties of mammalian albumins [6][7][8]. In previous communication, we have found that the four serum albumins from human, rabbit, porcine and bovine; i.e., HSA, RSA, PSA and BSA show similar aggregation patterns in the presence of methyl cyanide, with some clear indications of species-dependent variations [7].…”
Section: Introductionmentioning
confidence: 99%